Analysis of Fire Safety Depending on Opening Status of Gymnasium Door (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study, in an effort to minimize damage caused by fire in gymnasium, used XX gymnasium blueprint as a fire simulation program to perform fire safety analysis based on opening status of gymnasium door found at the time of fire. First, it was revealed that when the door was left completely closed and induced no airflow even a bit, the temperature surpassed 60℃at 45 seconds and peaked at about 200 seconds after the outbreak. Additionally in 100 seconds after the outbreak, the permissible visible distance of 5m was exceeded. Second, it was found that when the door was opened 50% and induced airflow, the temperature surpassed 60℃ at 50 seconds and peaked at around 180 seconds after the outbreak. In addition, in 120 seconds after the outbreak, the permissible visible distance of 5m was surpassed. Finally, it turned out that when the door was completely left open and induced airflow, the temperature exceeded 60℃ at 55 seconds and peaked around 180 seconds after the outbreak. What’s more, in 150 seconds after the outbreak, the permissible visible distance of 5m was surpassed.